Parenting sense of competence in at psychosocial risk families and child well-being - Nunes, C. (2019)
INTRODUCTION. Parenting sense of competence is a central construct to understand the dynamics and processes that occur within the family system. It is a major determinant of competent parenting behaviors, and it is closely linked to a healthy child development and their overall well-being. The aim of the present study is to obtain a better understanding of parenting sense of competence in Portuguese at-risk families and, more specifically, to analyze the relations between sociodemographic variables, perceived parenting efficacy, satisfaction with the parenting role and the child well-being. METHOD. The participants were 207 families (168 mothers and 39 fathers) receiving family preservation interventions in the Algarve (South of Portugal). The Parenting Sense of Competence Scale and a sociodemographic questionnaire were applied by trained interviewers, through an individual interview. Furthermore, the Child Well-Being Scales were filled by 21 case managers. RESULTS. Results showed that the majority of participants lived under a precarious economic and occupational situation, and had a low educational level. On average, families consisted of four people and of two children with 58,5% living below the national poverty line. Participants presented, on average, medium-high levels of perceived parenting efficacy and satisfaction, although they scored significantly higher on efficacy. We observed significant and positive correlations between parenting efficacy and satisfaction with all the child well-being dimensions (child well-being score, parental disposition and child performance) with the exception of household adequacy. DISCUSSION. These findings highlight the need to include the boosting of parental satisfaction and the readjustment of parental sense of efficacy as the primary aim of psycho-educational interventions in at-risk families. The implications for social policies for this vulnerable group are discussed.